Automatic metadata generation by utilising pre-existing metadata of related resources. (2nd March 2009) - Margaritopoulos, Merkourios; Margaritopoulos, Thomas; Kotini, Isabella; Manitsaris, Athanasios
Manual indexing of digital resources according to metadata standards is a laborious task. Methods and methodologies for automatically producing several parts of a resource's metadata provide valuable assistance to indexers and cataloguers by reducing the burden of their manual work. A methodology, which aims at identifying inference rules for the automatic generation of a resource's metadata, based on pre-existing metadata of its related resources, is introduced in this paper. Furthermore, the application of the methodology to the IEEE LOM standard and an experimental example on a working database of metadata, with a tool developed for this purpose, are demonstrated.